2016
DOI: 10.1016/j.artd.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Posterior-stabilized total knee arthroplasty: a matched pair analysis of a classic and its evolutional design

Abstract: BackgroundTotal knee arthroplasty (TKA) designs continue to be modified to optimize patient's outcome. This study was designed to compare clinical and radiological results of classic worldwide used TKA posterior-stabilized (PS) design to those of its recent evolution.MethodsA consecutive group of 100 patients undergoing TKA using a classic cemented fixed-bearing PS TKA system was matched by age, gender, body max index to 100 patients having the newer cemented fixed-bearing PS design, both by the same manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
4
29
1
Order By: Relevance
“…Patient reported outcome measures were promising in this study; all measures improved significantly up to one year after surgery. The OKS, one year after surgery in this study (41.1 points) is considerably higher when compared to other TKA cohorts [17–19]. Moreover, the results of the OKS in the current study are comparable to the results of the OKS of a partial knee arthroplasty [20, 21].…”
Section: Discussionsupporting
confidence: 67%
“…Patient reported outcome measures were promising in this study; all measures improved significantly up to one year after surgery. The OKS, one year after surgery in this study (41.1 points) is considerably higher when compared to other TKA cohorts [17–19]. Moreover, the results of the OKS in the current study are comparable to the results of the OKS of a partial knee arthroplasty [20, 21].…”
Section: Discussionsupporting
confidence: 67%
“…Recent reports, including those from the author's institution, have shown that the use of modern, third-generation TKA designs and instrumentation did not improve satisfaction rates in the TKA patient population. 5,6 Given this, studies show that using the minimum level of constraint to maintain stability has been related to a higher survivorship and patient satisfaction. 7 Many surgeons, however, fearing mid-flexion instability as a cause for early revision, 8 tend to over-constrain the knee resulting in loss of active ROM, point loading on the polyethylene insert, premature insert wear, and inferior implant survivorship.…”
Section: Introductionmentioning
confidence: 99%
“…32 Other authors have also shown increased range of motion with the ATTUNE system. 34 A comparison of ATTUNE and PFC TKA in Asian population showed improved Western Ontario and McMaster (WOMAC) scores and knee flexion in the ATTUNE group. 36 It is worth noting that these studies all have much smaller numbers in each group than our study.…”
Section: Discussionmentioning
confidence: 96%
“…30 This implant has also demonstrated a shorter length of stay and decreased likelihood of requiring a skilled nursing facility on discharge, thus reducing overall hospital costs. 31 Previous studies have shown improved patellofemoral symptoms and crepitus with the ATTUNE compared with the PFC Sigma, [32][33][34][35] although little difference in clinical outcome or satisfaction. 32 Other authors have also shown increased range of motion with the ATTUNE system.…”
Section: Discussionmentioning
confidence: 99%